Trouble with the cursed - Harrison, Kim, 1966- (Harrison, Kim, 1966- Hollows, 2022)
"Rachel Morgan must keep her friends close-and her enemies closer-in the next Hollows novel from #1 New York Times bestselling author Kim Harrison. Rachel Morgan, witch-born demon, has one unspoken rule: take chances, but pay for them yourself. With it, she has turned enemies into allies, found her place with her demon kin, and stepped up as the subrosa of Cincinnati-responsible for keeping the paranormal community at peace and in line. Life is ... good? Even better, her best friend, Ivy Tamwood, is returning home. Nothing's simple, though, and Ivy's not coming alone. The vampires' ruling council insists she escort one of the long undead, hell-bent on proving that Rachel killed Cincy's master vampire to take over the city. Which, of course, Rachel totally did not do. She only transformed her a little. With Rachel's friends distracted by their own lives and problems, she reaches out to a new ally for help-the demon Hodin. But this trickster has his own agenda. In the end, the only way for Rachel to save herself and the city may be to forge a new understanding with her estranged demon teacher, Al. There's just one problem: Al would sell his own soul to be rid of her ... "--